The Effect of Trichoderma on Heavy Metal Mobility and Uptake by Miscanthus giganteus, Salix sp., Phalaris arundinacea, and Panicum virgatum - Malgorzata J. Kacprzak; Karolina Rosikon; Krzysztof Fijalkowski; Anna Grobelak (Applied and Environmental Soil Science)
The effect of land application of biomaterials based on two strains of Trichoderma fungus on phytoremediation processes was studied. Six metals (Cd, Cr, Cu, Pb, Zn, and Ni) were analysed in soil and soil leachate as well as in plant tissues. The translocation index (Ti) and metal bioconcentration factors (BCF) calculated for the inoculated plants were increased compared to the noninoculated control, except for Pb and Salix sp. Simultaneously, the mobilisation of metals in soil solution as an effect of biomaterials was noted. The highest values of Ti—339% (for Cr), 190% (for Ni), and 110% (for Cu)—were achieved for the combination Miscanteus giganteus and Trichoderma MSO1. The results indicated that the application of fungus has positive effects on increasing the biomass, soil parameters (C, N, and P), and solubility of heavy metals in soil and therefore in enhancing phytoextraction for Miscanthus giganteus L., Panicum virgatum L., Phalaris arundinacea L., and Salix sp.